Analisis Keberlanjutan Wisata Bangsring Underwater Kabupaten Banyuwangi - Adi Wijaya, Jemi Cahya; Kanom, Kanom; Darmawan, Randhi Nanang; Mecha, I Putu Sudhyana (Pusat Penelitian dan Pengabdian Kepada Masyarakat, Institut Pariwisata Trisakti, 2023)
Bangsring Underwater is a marine tourism area that adopts the concept of ecotourism in Banyuwangi Regency. It has several challenges that must be faced. During the rainy season, the sea water in Bangsring Underwater becomes cloudy, the sea waves are high, and usually there is a lot of garbage in the snorkeling and diving areas. Besides that, the coral reefs are also getting more and more damaged due to accidental visitors while doing snorkeling. The purpose of this study was to evaluate the sustainability status of Bangsring Underwater in terms of ecological dimensions, economic dimensions, socio-cultural dimensions, legal and institutional dimensions as well as infrastructure and technology dimensions. This type of research is descriptive research with a quantitative approach. The analytical method used in this study is Multi Dimensional Scaling (MDS) with rapid appraisal analysis tools. The results of this study indicate that the sustainability status of Bangsring Underwater in Banyuwangi Regency is stated to be quite sustainable with a sustainability status index value of 74.03 in terms of ecological dimensions, economic dimensions, socio-cultural dimensions, legal and institutional dimensions as well as infrastructure and technology dimensions. Keywords: Bangsring Underwater, Banyuwangi Regency, Rapid Appraisal, Ecotourism